Analisis Peningkatan Kemampuan Berpikir Tingkat Tinggi Siswa Kelas XII dalam Pembelajaran Materi Dimensi Tiga - Sabam Isay Sianipar; Putri Isnaini; Nazwa Azzahra; Cintya Agatha Rumahombar; Chelsea Natalia Panjaitan (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
This study aims to analyze the improvement of Higher Order Thinking Skills (HOTS) through mathematics learning on the Three-Dimensional Geometry topic in Grade XII of Yayasan Pendidikan Al-Fattah Medan. HOTS is a crucial aspect of 21st-century education because it helps students develop critical, creative, logical, and reflective thinking skills in addressing complex problems. In the context of mathematics learning, particularly in spatial geometry, mastering HOTS not only supports students in understanding abstract concepts but also in applying them to real-life situations. This study employed a descriptive qualitative method with instruments consisting of a pre-test, post-test, and an open-ended questionnaire to explore students’ understanding and learning experiences. The findings revealed a significant improvement, where the average pre-test score of 7 increased to 52.21 in the post-test. This result highlights that the implementation of HOTS-based learning strategies is effective in enhancing students’ comprehension of distance, angles, and point positions in space, while simultaneously strengthening their analytical, evaluative, and creative abilities. The study implies the importance of adopting innovative learning strategies oriented toward HOTS development to improve the quality of mathematics education and prepare students for global challenges.